Social influence on age and reproduction reduced lifespan and fecundity in multi queen ant colonies - Schrempf, Alexandra; Cremer, Sylvia; Heinze, Jürgen (Journal of Evolutionary Biology)
Evolutionary theories of ageing predict that life span increases with decreasing extrinsic mortality, and life span variation among queens in ant species seems to corroborate this prediction: queens, which are the only reproductive in a colony, live much longer than queens in multi-queen colonies. The latter often inhabit ephemeral nest sites and accordingly are assumed to experience a higher mortality risk. Yet, all prior studies compared queens from different single- and multi-queen species. Here, we demonstrate an effect of queen number on longevity and fecundity within a single, socially plastic species, where queens experience the similar level of extrinsic mortality. Queens from single- and two-queen colonies had significantly longer lifespan and higher fecundity than queens living in associations of eight queens. As queens also differ neither in morphology nor the mode of colony foundation, our study shows that the social environment itself strongly affects ageing rate.

Split based computation of majority rule supertrees - Kupczok, Anne (BMC Evolutionary Biology)
Background: Supertree methods combine overlapping input trees into a larger supertree. Here, I consider split-based supertree methods that first extract the split information of the input trees and subsequently combine this split information into a phylogeny. Well known split-based supertree methods are matrix representation with parsimony and matrix representation with compatibility. Combining input trees on the same taxon set, as in the consensus setting, is a well-studied task and it is thus desirable to generalize consensus methods to supertree methods. Results: Here, three variants of majority-rule (MR) supertrees that generalize majority-rule consensus trees are investigated. I provide simple formulas for computing the respective score for bifurcating input- and supertrees. These score computations, together with a heuristic tree search minmizing the scores, were implemented in the python program PluMiST (Plus- and Minus SuperTrees) available from http://www.cibiv.at/software/ plumist. The different MR methods were tested by simulation and on real data sets. The search heuristic was successful in combining compatible input trees. When combining incompatible input trees, especially one variant, MR(-) supertrees, performed well. Conclusions: The presented framework allows for an efficient score computation of three majority-rule supertree variants and input trees. I combined the score computation with a heuristic search over the supertree space. The implementation was tested by simulation and on real data sets and showed promising results. Especially the MR(-) variant seems to be a reasonable score for supertree reconstruction. Generalizing these computations to multifurcating trees is an open problem, which may be tackled using this framework.

Reconstructing eight decades of genetic variation in an isolated Danish population of the large blue butterfly Maculinea arion - Ugelvig, Line V; Nielsen, Per; Boomsma, Jacobus; Nash, David (BMC Evolutionary Biology)
Background: Fragmentation of terrestrial ecosystems has had detrimental effects on metapopulations of habitat specialists. Maculinea butterflies have been particularly affected because of their specialized lifecycles, requiring both specific food-plants and host-ants. However, the interaction between dispersal, effective population size, and long-term genetic erosion of these endangered butterflies remains unknown. Using non-destructive sampling, we investigated the genetic diversity of the last extant population of M. arion in Denmark, which experienced critically low numbers in the 1980s. Results: Using nine microsatellite markers, we show that the population is genetically impoverished compared to nearby populations in Sweden, but less so than monitoring programs suggested. Ten additional short repeat microsatellites were used to reconstruct changes in genetic diversity and population structure over the last 77 years from museum specimens. We also tested amplification efficiency in such historical samples as a function of repeat length and sample age. Low population numbers in the 1980s did not affect genetic diversity, but considerable turnover of alleles has characterized this population throughout the time-span of our analysis. Conclusions: Our results suggest that M. arion is less sensitive to genetic erosion via population bottlenecks than previously thought, and that managing clusters of high quality habitat may be key for long-term conservation.

Semi supervised kernel canonical correlation analysis with application to human fMRI - Blaschko, Matthew; Shelton, Jacquelyn; Bartels, Andreas; Lampert, Christoph; Gretton, Arthur (Pattern Recognition Letters)
Kernel canonical correlation analysis (KCCA) is a general technique for subspace learning that incorporates principal components analysis (PCA) and Fisher linear discriminant analysis (LDA) as special cases. By finding directions that maximize correlation, KCCA learns representations that are more closely tied to the underlying process that generates the data and can ignore high-variance noise directions. However, for data where acquisition in one or more modalities is expensive or otherwise limited, KCCA may suffer from small sample effects. We propose to use semi-supervised Laplacian regularization to utilize data that are present in only one modality. This approach is able to find highly correlated directions that also lie along the data manifold, resulting in a more robust estimate of correlated subspaces. Functional magnetic resonance imaging (fMRI) acquired data are naturally amenable to subspace techniques as data are well aligned. fMRI data of the human brain are a particularly interesting candidate. In this study we implemented various supervised and semi-supervised versions of KCCA on human fMRI data, with regression to single and multi-variate labels (corresponding to video content subjects viewed during the image acquisition). In each variate condition, the semi-supervised variants of KCCA performed better than the supervised variants, including a supervised variant with Laplacian regularization. We additionally analyze the weights learned by the regression in order to infer brain regions that are important to different types of visual processing.

The relation between reproductive value and genetic contribution - Barton, Nicholas H; Etheridge, Alison (Genetics)
What determines the genetic contribution that an individual makes to future generations? With biparental reproduction, each individual leaves a 'pedigree' of descendants, determined by the biparental relationships in the population. The pedigree of an individual constrains the lines of descent of each of its genes. An individual's reproductive value is the expected number of copies of each of its genes that is passed on to distant generations conditional on its pedigree. For the simplest model of biparental reproduction analogous to the Wright-Fisher model, an individual's reproductive value is determined within ~10 generations, independent of population size. Partial selfing and subdivision do not greatly slow this convergence. Our central result is that the probability that a gene will survive is proportional to the reproductive value of the individual that carries it, and that conditional on survival, after a few tens of generations, the distribution of the number of surviving copies is the same for all individuals, whatever their reproductive value. These results can be generalized to the joint distribution of surviving blocks of ancestral genome. Selection on unlinked loci in the genetic background may greatly increase the variance in reproductive value, but the above results nevertheless still hold. The almost linear relationship between survival probability and reproductive value also holds for weakly favored alleles. Thus, the influence of the complex pedigree of descendants on an individual's genetic contribution to the population can be summarized through a single number: its reproductive value.

The contribution of statistical physics to evolutionary biology - de Vladar, Harold; Barton, Nicholas H (Trends in Ecology and Evolution)
Evolutionary biology shares many concepts with statistical physics: both deal with populations, whether of molecules or organisms, and both seek to simplify evolution in very many dimensions. Often, methodologies have undergone parallel and independent development, as with stochastic methods in population genetics. Here, we discuss aspects of population genetics that have embraced methods from physics: non-equilibrium statistical mechanics, travelling waves and Monte-Carlo methods, among others, have been used to study polygenic evolution, rates of adaptation and range expansions. These applications indicate that evolutionary biology can further benefit from interactions with other areas of statistical physics; for example, by following the distribution of paths taken by a population through time

In vivo analysis of uropod function during physiological T cell trafficking - Soriano, Silvia; Hons, Miroslav; Schumann, Kathrin; Kumar, Varsha; Dennier, Timo; Lyck, Ruth; Sixt, Michael K; Stein, Jens (Journal of Immunology)
Migrating lymphocytes acquire a polarized phenotype with a leading and a trailing edge, or uropod. Although in vitro experiments in cell lines or activated primary cell cultures have established that Rho-p160 coiled-coil kinase (ROCK)-myosin II-mediated uropod contractility is required for integrin de-adhesion on two-dimensional surfaces and nuclear propulsion through narrow pores in three-dimensional matrices, less is known about the role of these two events during the recirculation of primary, nonactivated lymphocytes. Using pharmacological antagonists of ROCK and myosin II, we report that inhibition of uropod contractility blocked integrin-independent mouse T cell migration through narrow, but not large, pores in vitro. T cell crawling on chemokine-coated endothelial cells under shear was severely impaired by ROCK inhibition, whereas transendothelial migration was only reduced through endothelial cells with high, but not low, barrier properties. Using three-dimensional thick-tissue imaging and dynamic two-photon microscopy of T cell motility in lymphoid tissue, we demonstrated a significant role for uropod contractility in intraluminal crawling and transendothelial migration through lymph node, but not bone marrow, endothelial cells. Finally, we demonstrated that ICAM-1, but not anatomical constraints or integrin-independent interactions, reduced parenchymal motility of inhibitor-treated T cells within the dense lymphoid microenvironment, thus assigning context-dependent roles for uropod contraction during lymphocyte recirculation.

Spatial waves of advance with bistable dynamics: Cytoplasmic and genetic analogues of Allee effects - Barton, Nicholas H; Turelli, Michael (American Naturalist)
Unlike unconditionally advantageous “Fisherian” variants that tend to spread throughout a species range once introduced anywhere, “bistable” variants, such as chromosome translocations, have two alternative stable frequencies, absence and (near) fixation. Analogous to populations with Allee effects, bistable variants tend to increase locally only once they become sufficiently common, and their spread depends on their rate of increase averaged over all frequencies. Several proposed manipulations of insect populations, such as using Wolbachia or “engineered underdominance” to suppress vector-borne diseases, produce bistable rather than Fisherian dynamics. We synthesize and extend theoretical analyses concerning three features of their spatial behavior: rate of spread, conditions to initiate spread from a localized introduction, and wave stopping caused by variation in population densities or dispersal rates. Unlike Fisherian variants, bistable variants tend to spread spatially only for particular parameter combinations and initial conditions. Wave initiation requires introduction over an extended region, while subsequent spatial spread is slower than for Fisherian waves and can easily be halted by local spatial inhomogeneities. We present several new results, including robust sufficient conditions to initiate (and stop) spread, using a one-parameter cubic approximation applicable to several models. The results have both basic and applied implications.

Genetic drift widens the expected cline but narrows the expected cline width - Polechova, Jitka; Barton, Nicholas H (Genetics)
Random genetic drift shifts clines in space, alters their width, and distorts their shape. Such random fluctuations complicate inferences from cline width and position. Notably, the effect of genetic drift on the expected shape of the cline is opposite to the naive (but quite common) misinterpretation of classic results on the expected cline. While random drift on average broadens the overall cline in expected allele frequency, it narrows the width of any particular cline. The opposing effects arise because locally, drift drives alleles to fixation—but fluctuations in position widen the expected cline. The effect of genetic drift can be predicted from standardized variance in allele frequencies, averaged across the habitat: 〈F〉. A cline maintained by spatially varying selection (step change) is expected to be narrower by a factor of relative to the cline in the absence of drift. The expected cline is broader by the inverse of this factor. In a tension zone maintained by underdominance, the expected cline width is narrower by about 1 – 〈F〉relative to the width in the absence of drift. Individual clines can differ substantially from the expectation, and we give quantitative predictions for the variance in cline position and width. The predictions apply to clines in almost one-dimensional circumstances such as hybrid zones in rivers, deep valleys, or along a coast line and give a guide to what patterns to expect in two dimensions.

Effect of oceanographic barriers and overfishing on the population genetic structure of the European spiny lobster Palinurus elephas - Palero, Ferran; Abello, Pere; Macpherson, Enrique; Beaumont, Mark; Pascual, Marta (Biological Journal of the Linnean Society)
Defining population structure and genetic diversity levels is of the utmost importance for developing efficient conservation strategies. Overfishing has caused mean annual catches of the European spiny lobster (Palinurus elephas) to decrease alarmingly along its distribution area. In this context, there is a need for comprehensive studies aiming to evaluate the genetic health of the exploited populations. The present study is based on a set of ten nuclear markers amplified in 331 individuals from ten different localities covering most of P. elephas distribution area. Samples from Atlantic and Mediterranean basins showed small but significant differences, indicating that P. elephas populations do not behave as a single panmictic unit but form two partially-overlapping groups. Despite intense overfishing, our dataset did not recover a recent bottleneck signal, and instead showed a large and stable historical effective size. This result could be accounted for by specific life-history traits (reproduction and longevity) and the limitations of molecular markers in covering recent timescales for nontemporal samples. The findings of the present study emphasize the need to integrate information on effective population sizes and life-history parameters when evaluating population connectivity levels from genetic data.

Defective neuroepithelial cell cohesion affects tangential branchiomotor neuron migration in the zebrafish neural tube - Stockinger, Petra; Heisenberg, Carl-Philipp J; Maître, Jean-Léon (Development)
Facial branchiomotor neurons (FBMNs) in zebrafish and mouse embryonic hindbrain undergo a characteristic tangential migration from rhombomere (r) 4, where they are born, to r6/7. Cohesion among neuroepithelial cells (NCs) has been suggested to function in FBMN migration by inhibiting FBMNs positioned in the basal neuroepithelium such that they move apically between NCs towards the midline of the neuroepithelium instead of tangentially along the basal side of the neuroepithelium towards r6/7. However, direct experimental evaluation of this hypothesis is still lacking. Here, we have used a combination of biophysical cell adhesion measurements and high-resolution time-lapse microscopy to determine the role of NC cohesion in FBMN migration. We show that reducing NC cohesion by interfering with Cadherin 2 (Cdh2) activity results in FBMNs positioned at the basal side of the neuroepithelium moving apically towards the neural tube midline instead of tangentially towards r6/7. In embryos with strongly reduced NC cohesion, ectopic apical FBMN movement frequently results in fusion of the bilateral FBMN clusters over the apical midline of the neural tube. By contrast, reducing cohesion among FBMNs by interfering with Contactin 2 (Cntn2) expression in these cells has little effect on apical FBMN movement, but reduces the fusion of the bilateral FBMN clusters in embryos with strongly diminished NC cohesion. These data provide direct experimental evidence that NC cohesion functions in tangential FBMN migration by restricting their apical movement.

The role of adhesion energy in controlling cell-cell contacts - Maître, Jean-Léon; Heisenberg, Carl-Philipp J (Current Opinion in Cell Biology)
Recent advances in microscopy techniques and biophysical measurements have provided novel insight into the molecular, cellular and biophysical basis of cell adhesion. However, comparably little is known about a core element of cell–cell adhesion—the energy of adhesion at the cell–cell contact. In this review, we discuss approaches to understand the nature and regulation of adhesion energy, and propose strategies to determine adhesion energy between cells in vitro and in vivo.

Competition and opportunity shape the reproductive tactics of males in the ant Cardiocondyla obscurior - Cremer, Sylvia; Schrempf, Alexandra; Heinze, Jürgen (PLoS One)
Context-dependent adjustment of mating tactics can drastically increase the mating success of behaviourally flexible animals. We used the ant Cardiocondyla obscurior as a model system to study adaptive adjustment of male mating tactics. This species shows a male diphenism of wingless fighter males and peaceful winged males. Whereas the wingless males stay and exclusively mate in the maternal colony, the mating behaviour of winged males is plastic. They copulate with female sexuals in their natal nests early in life but later disperse in search for sexuals outside. In this study, we observed the nest-leaving behaviour of winged males under different conditions and found that they adaptively adjust the timing of their dispersal to the availability of mating partners, as well as the presence, and even the type of competitors in their natal nests. In colonies with virgin female queens winged males stayed longest when they were the only male in the nest. They left earlier when mating partners were not available or when other males were present. In the presence of wingless, locally mating fighter males, winged males dispersed earlier than in the presence of docile, winged competitors. This suggests that C. obscurior males are capable of estimating their local breeding chances and adaptively adjust their dispersal behaviour in both an opportunistic and a risk-sensitive way, thus showing hitherto unknown behavioural plasticity in social insect males.

The formation of the Bicoid morphogen gradient requires protein movement from anteriorly localized source - Little, Shawn; Tkacik, Gasper; Kneeland, Thomas; Wieschaus, Eric; Gregor, Thomas (PLoS Biology)
The Bicoid morphogen gradient directs the patterning of cell fates along the anterior-posterior axis of the syncytial Drosophila embryo and serves as a paradigm of morphogen-mediated patterning. The simplest models of gradient formation rely on constant protein synthesis and diffusion from anteriorly localized source mRNA, coupled with uniform protein degradation. However, currently such models cannot account for all known gradient characteristics. Recent work has proposed that bicoid mRNA spatial distribution is sufficient to produce the observed protein gradient, minimizing the role of protein transport. Here, we adapt a novel method of fluorescent in situ hybridization to quantify the global spatio-temporal dynamics of bicoid mRNA particles. We determine that >90% of all bicoid mRNA is continuously present within the anterior 20% of the embryo. bicoid mRNA distribution along the body axis remains nearly unchanged despite dynamic mRNA translocation from the embryo core to the cortex. To evaluate the impact of mRNA distribution on protein gradient dynamics, we provide detailed quantitative measurements of nuclear Bicoid levels during the formation of the protein gradient. We find that gradient establishment begins 45 minutes after fertilization and that the gradient requires about 50 minutes to reach peak levels. In numerical simulations of gradient formation, we find that incorporating the actual bicoid mRNA distribution yields a closer prediction of the observed protein dynamics compared to modeling protein production from a point source at the anterior pole. We conclude that the spatial distribution of bicoid mRNA contributes to, but cannot account for, protein gradient formation, and therefore that protein movement, either active or passive, is required for gradient formation.

Modern ionotropic glutamate receptor with a K+ selectivity signature sequence - Janovjak, Harald L; Sandoz, Guillaume; Isacoff, Ehud (Nature Communications)
Glutamate is the major excitatory neurotransmitter in the mammalian central nervous system and gates non-selective cation channels. The origins of glutamate receptors are not well understood as they differ structurally and functionally from simple bacterial ligand-gated ion channels. Here we report the discovery of an ionotropic glutamate receptor that combines the typical eukaryotic domain architecture with the 'TXVGYG' signature sequence of the selectivity filter found in K+ channels. This receptor exhibits functional properties intermediate between bacterial and eukaryotic glutamate-gated ion channels, suggesting a link in the evolution of ionotropic glutamate receptors.

Morphology evolution of Cu2−xS nanoparticles: from spheres to dodecahedrons - Li, Wenhua; Shavel, Alexey; Guzman, Roger; Rubio Garcia, Javier; Flox, Cristina; Fan, Jiandong; Cadavid, Doris; Ibáñez, Maria; Arbiol, Jordi; Morante, Joan; Cabot, Andreu (Chemical Communications)
An oriented attachment and growth mechanism allows an accurate control of the size and morphology of Cu2-xS nanocrystals, from spheres and disks to tetradecahedrons and dodecahedrons. The synthesis conditions and the growth mechanism are detailed here.

Arithmetic harmonic analysis on character and quiver varieties - Tamas Hausel; Letellier, Emmanuel; Rodríguez Villegas, Fernando (Duke Mathematical Journal)
We propose a general conjecture for the mixed Hodge polynomial of the generic character varieties of representations of the fundamental group of a Riemann surface of genus g to GLn(C) with fixed generic semisimple conjugacy classes at k punctures. This conjecture generalizes the Cauchy identity for Macdonald polynomials and is a common generalization of two formulas that we prove in this paper. The first is a formula for the E-polynomial of these character varieties which we obtain using the character table of GLn(Fq). We use this formula to compute the Euler characteristic of character varieties. The second formula gives the Poincaré polynomial of certain associated quiver varieties which we obtain using the character table of gln(Fq). In the last main result we prove that the Poincaré polynomials of the quiver varieties equal certain multiplicities in the tensor product of irreducible characters of GLn(Fq). As a consequence we find a curious connection between Kac-Moody algebras associated with comet-shaped, and typically wild, quivers and the representation theory of GLn(Fq).

Multimode mediated qubit-qubit coupling and dark-state symmetries in circuit quantum electrodynamics - Filipp, Stefan; Göppl, M; Johannes Fink; Baur, Matthias P; Bianchetti, R; Steffen, L. Kraig; Wallraff, Andreas (Physical Review A - Atomic, Molecular, and Optical Physics)
Microwave cavities with high quality factors enable coherent coupling of distant quantum systems. Virtual photons lead to a transverse interaction between qubits when they are nonresonant with the cavity but resonant with each other. We experimentally investigate the inverse scaling of the interqubit coupling with the detuning from a cavity mode and its proportionality to the qubit-cavity interaction strength. We demonstrate that the enhanced coupling at higher frequencies is mediated by multiple higher-harmonic cavity modes. Moreover, we observe dark states of the coupled qubit-qubit system and analyze their relation to the symmetry of the applied driving field at different frequencies.

Adaptive response and enlargement of dynamic range - Tamar Friedlander; Brenner, Naama (Mathematical Biosciences and Engineering)
Many membrane channels and receptors exhibit adaptive, or desensitized, response to a strong sustained input stimulus, often supported by protein activity-dependent inactivation. Adaptive response is thought to be related to various cellular functions such as homeostasis and enlargement of dynamic range by background compensation. Here we study the quantitative relation between adaptive response and background compensation within a modeling framework. We show that any particular type of adaptive response is neither sufficient nor necessary for adaptive enlargement of dynamic range. In particular a precise adaptive response, where system activity is maintained at a constant level at steady state, does not ensure a large dynamic range neither in input signal nor in system output. A general mechanism for input dynamic range enlargement can come about from the activity-dependent modulation of protein responsiveness by multiple biochemical modification, regardless of the type of adaptive response it induces. Therefore hierarchical biochemical processes such as methylation and phosphorylation are natural candidates to induce this property in signaling systems.

The number of equilibria in the diallelic Levene model with multiple demes - Sebastian Novak (Theoretical Population Biology)
The Levene model is the simplest mathematical model to describe the evolution of gene frequencies in spatially subdivided populations. It provides insight into how locally varying selection promotes a population’s genetic diversity. Despite its simplicity, interesting problems have remained unsolved even in the diallelic case. In this paper we answer an open problem by establishing that for two alleles at one locus and J demes, up to 2J−1 polymorphic equilibria may coexist. We first present a proof for the case of stable monomorphisms and then show that the result also holds for protected alleles. These findings allow us to prove that any odd number (up to 2J−1) of equilibria is possible, before we extend the proof to even numbers. We conclude with some numerical results and show that for J>2, the proportion of parameter space affording this maximum is extremely small.